Peer Review and the Three Rs: A Challenge to Integrity?. Issue 4 (September 2015) - Balls, Michael
Peer review is undoubtedly an imperfect process, but there is no other acceptable way of attempting to ensure the highest standards in research and the publication of opinions and results